AGAMA DAN MULTIKULTUR: PERAN AGAMA MEWUJUDKAN MULTIKULTURALISME DI INDONESIA - Ida Bagus Purnawan (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2013)
The difference and plurality are necessity condition that must and should be accepted by everyone in his life on earth as human beings. It is a true reality that we know it clearly. How to manage this reality is a longlife problem.One of the efforts is empowering the role of religion. The role of religion in realizing multiculturalism in Indonesia can be reached by building mutual awarenes through the efforts of multiculturalism consciousness transformation into a national identity based on the reality of plurality in Indonesia. The Unity in Diversity as an ideal text always need to be read at any occasion because, in principle, the identity is never final. Likewise, efforts to build a national integration based on multiculturalism by encouraging public awareness using their constitutional rights to assembly, association, and expression in order to fight for the rights of justice, liberty, equality, and actively participated in the development.